I$1 (Bm a great big monster truck! s - Steele, Michael Anthony; Mones, Isidre; Mones, Marc (New York : Scholastic, 2004)
"I was built extra big for power and speed. I$1 (Bm an excellent racer. I$1 (Bm also great at crushing cars with my giant wheels. I love to show off for the crowd!"s
"Tonka."
Keywords: Monster trucks -- Fiction